The Efficacy of Ultrasound-guided Single Shot Erector Spinae Plane Block in Post-operative Pain Management after Thoracic Surgery in the First 48 Hours: A Prospective Descriptive Study - Kaewanuchit, Areerat (Thai Journal of Anesthesiology, 2021)
Background: Postoperative pain management after thoracic surgery is essential and can lead to serious postoperative complications if not appropriately managed. Ultrasound-guided thoracic erector spinae plane block (US-ESP block) has gained more popularity for postoperative pain management in thoracic surgery. However, there was no data on postoperative opioid consumptions and pain scores in Thailand. Objectives: The main objective of this study was to study the efficacy of single shot ultrasound-guided erector spinae plane block for postoperative pain management after thoracic surgery Methods:A prospective descriptive study was conducted in patients who underwent elective thoracic surgery at Central Chest Institute of Thailand with operative time of one hour or more during August 1 to December 30, 2020. The ultrasound-guided ESP at the level of the 5th thoracic vertebra was performed at the end of surgery with 1% xylocaine and 0.25% bupivacaine with adrenaline 10 and 20 mL, respectively. The efficacy of ESP was evaluated by 1) pain scores at 15, 30 minutes and 1, 2, 4, 8, 16, 24, and 48 hours postoperatively 2) time to first dose of postoperative morphine requirement 3) morphine consumption at 24 and 48 hours postoperatively. Results: Sixty two patients were included in the study. Thirty five cases (56.5%) were video-assisted thoracoscopic surgery (VATS). The mean duration of surgery was 170.5 minutes (ranges from 123.75-197.5 min). Thirty-nine (62.9%) patients did not receive any morphine at the recovery room. There were no patients who experienced severe pain in 48 hours postoperatively. Most of patients received first dose of morphine at 8 hours after the operation. The average of pain score at the first morphine requirement was 5. The average 24 and 48 hours postoperative morphine consumption was 7 and 7.19 mg respectively. Conclusion: The combination of the thoracic erector spinae plane block at the 5th thoracic level after thoracic surgery plus intraoperative intravenous morphine is an effective technique for decreasing postoperative pain to mild or moderate level within 48 hours and reduces morphine requirement especially in 8 hours after the operation.